Clinical high risk for psychosis: the association between momentary stress, affective and psychotic symptoms. (5th March 2017) - van der Steen, Y.; Gimpel‐Drees, J.; Lataster, T.; Viechtbauer, W.; Simons, C. J. P.; Lardinois, M.; Michel, T. M.; Janssen, B.; Bechdolf, A.; Wagner, M.; Myin‐Germeys, I.
Abstract : Objective: The aim of this study was to assess associations between momentary stress and both affective and psychotic symptoms in everyday life of individuals at clinical high risk (CHR), compared to chronic psychotic patients and healthy controls, in search for evidence of early stress sensitization. It also assessed whether psychotic experiences were experienced as stressful. Method: The experience sampling method was used to measure affective and psychotic reactivity to everyday stressful activities, events and social situations in 22 CHR patients, 24 patients with a psychotic disorder and 26 healthy controls. Results: Multilevel models showed significantly larger associations between negative affect (NA) and activity‐related stress for CHR patients than for psychotic patients ( P = 0.008) and for CHR compared to controls ( P < 0.001). Similarly, the association between activity‐related stress and psychotic symptoms was larger in CHR than in patients ( P = 0.02). Finally, the association between NA and symptoms ( P < 0.001) was larger in CHR than in patients. Conclusion: Stress sensitization seems to play a role particularly in the early phase of psychosis development as results suggest that CHR patients are more sensitive to daily life stressors than psychotic patients. In this early phase, psychotic experiences also contributed to the experience of stress.